Knowledge and practice of women attended in primary health care about Papanicolau test / Conhecimento e prática de mulheres atendidas na atenção primária a saúde sobre o exame Papanicolau - Leticia Almeida Silva; Ananda Santos Freitas; Bruna Carolynne Tôrres Müller; Magnólia de Jesus Sousa Magalhães (Universidade Federal do Estado do Rio de Janeiro, 2021)
Objective: to evaluate the knowledge and practice of women assisted in Basic Health Units in relation to the Pap smear. Method: this is a quantitative, descriptive study with a cross-sectional design. 320 women living in the area covered by three Basic Health Units in the city of Caxias-MA were interviewed. Results: although almost all of the women interviewed heard about the Pap smear exam 311 (97.2%), more than half of them had inadequate knowledge 233 (72.8%). It was also noticed that despite the fact that more than half were classified as having inadequate knowledge, most women had an adequate practice 187 (58.44%). Conclusion: thus, this study showed that there was no association between the level of knowledge and the practice of women. Therefore, there is a precarious knowledge of the majority of women about the cervical cancer preventive exam, resulting in an erroneous attribution about its purposes.